Experimental and computational analysis for thermo-erosive stability assessment of ZrB2-SiC based multiphase composites. (November 2019) - Purwar, Anupam; Ariharan, S.; Basu, Bikramjit; B., Venkata Manoj Kumar
Abstract: High temperature erosion tests were conducted on spark plasma sintered ZrB2 -SiC based multiphase ceramic composites at 1073 K in thermo-erosive environment for 1200 s with a net energy deposition per unit area of 50.5 MJ/m 2 . The thermo-erosive mechanisms were qualitatively discussed using XRD and SEM-EDS analyses. Efforts were made to assess feasibility of identified reactions at the computed temperatures to support reaction mechanism for oxide formation in eroded region. Finite element (FE) analysis with high-quality structural elements was used to determine the spatial temperature and stress distribution in the eroded region. Taken together, the present study highlights the significance of combined approach of computational and experimental analysis in understanding the thermo-erosive-structural stability in applications where erosion can limit the performance of ceramic composites. Highlights: For the first time, the present work demonstrates the significance of computational analysis in understanding the wear behavior of ZrB2 -18SiC and ZrB2 -18SiC-10Ti composites in high temperature erosion conditions. The reduced effect of mechanical properties improvement on high temperature erosion wear resistance could be explained by stress distribution in eroded regions. As per the computational analysis, almost one order of magnitude higher stresses is found in eroded region of ZrB2 -18SiC-10Ti composite compared to ZrB2 -18SiC composite.